An occupancy approach to monitoring regent honeyeaters. Issue 4 (7th April 2017) - Crates, Ross; Terauds, Aleks; Rayner, Laura; Stojanovic, Dejan; Heinsohn, Robert; Ingwersen, Dean; Webb, Matthew
ABSTRACT: Conservation of rare and highly mobile species is frequently limited by a lack of monitoring data. Critically endangered regent honeyeaters ( Anthochaera phrygia, population 350–400) pose a substantial conservation challenge because of their high mobility and irregular settlement throughout their estimated 600, 000‐km 2 range. Given an ongoing population decline, enhanced monitoring efforts to inform population management are needed. We conducted an occupancy survey of regent honeyeaters and other nectarivores over 880 km 2 of the species' core range in New South Wales, Australia, during spring 2015. We located approximately 70 regent honeyeaters, potentially representing 20% of the population. Presence of regent honeyeaters was best predicted by high local nectar abundance. Detectability of regent honeyeaters when breeding (0.59) was similar to common, co‐occurring nectarivores and was sufficient to distinguish absence from non‐detection. For rare and highly mobile species, monitoring approaches that prioritize sampling extent over site visit duration and explicitly accommodate their life‐history attributes can provide valuable population data, with subsequent benefits for conservation. © 2017 The Wildlife Society. Abstract : We present an occupancy monitoring approach that explicitly accounts for the life history of the semi‐nomadic and critically endangered regent honeyeater. Although they may be very rare, we show that regent honeyeaters are not cryptic, tend to be spatially autocorrelated in their distribution, and that a spatially intensive and extensive sampling design can return valuable population data to enhance conservation management.